Implementation of the Project to Strengthen the Student Profile of Pancasila Through MMB (Muhammadiyah Advancing Talent) Activities at SMP Muhammadiyah 8 Batu - Suwandi, Khansa Naura Mumtaza; Widodo, Rohmad; Syahri, M. (Universitas Negeri Gorontalo, 2025)
This study aims to describe and examine the implementation of the Pancasila student profile strengthening project through Muhammadiyah Advancing Talent activities at SMP Muhammadiyah 8 Batu. The purpose of this study is to implement a project to strengthen the profile of Pancasila students through the activities of Muhammadiyah Advancing Talent at SMP Muhammadiyah 8 Batu. The method used in this study is a qualitative approach with a descriptive type, data collection techniques through observation, interviews and documentation. The results of the study show that the form of implementation of the Pancasila student profile strengthening project is packaged through the Muhammadiyah Advancing Talent activity which contains local wisdom with the theme